2020
DOI: 10.1101/2020.09.22.20199703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of sTREM-1 in COVID-19 patients: a biomarker for disease severity and mortality

Abstract: Background: The uncontrolled inflammatory response plays a critical role in the novel coronavirus disease (COVID-19) and triggering receptor expressed on myeloid cells-1 (TREM-1) is thought to be intricate to inflammatory signal amplification. This study aims to investigate the association between soluble TREM-1 (sTREM-1) and COVID-19 as a prognostic biomarker to predict the disease severity, lethality and clinical management.Methods: We enrolled 91 patients with COVID-19 in domiciliary care (44 patients) or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…TREM-1 has emerged as a key molecule during inflammatory diseases, promoting complex effects on cells of the immune system and exacerbating the host response [7,8]. Studies have explored the role of TREM-1 in inducing inflammation in multiple contexts, such as sepsis [9,21], cancer [22], viral infections [23,24], and others non-infectious diseases [25,26]. However, the role of TREM-1 signaling in innate immunity against parasite infections and its underlying mechanisms remain unknown [13,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 has emerged as a key molecule during inflammatory diseases, promoting complex effects on cells of the immune system and exacerbating the host response [7,8]. Studies have explored the role of TREM-1 in inducing inflammation in multiple contexts, such as sepsis [9,21], cancer [22], viral infections [23,24], and others non-infectious diseases [25,26]. However, the role of TREM-1 signaling in innate immunity against parasite infections and its underlying mechanisms remain unknown [13,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sTREM-1 is an important prognostic marker in diseases that also develop severe inflammatory pathways, such as sepsis and AIDS [10,15,17,18]. Recently, our group [19] and other works [20,21] suggested that sTREM-1 levels are related to COVID-19 severity and may serve as early triage tools for patients with adverse outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…Coronavirus disease (COVID- 19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), became a global public health problem due to the important frequencies of mortality. Approximately 80% of patients infected with SARS-CoV-2 will exhibit mild symptoms or remain asymptomatic.…”
Section: Introductionmentioning
confidence: 99%